Physics Learning Innovation: Song and Animation-Based Media as a Learning Solution for Mirrors and Lenses for Junior High School Students - Zakiyah, Zakiyah; Boonma , Kantida; Collado, Resty (Journal of Educational Technology and Learning Creativity, 2024)
Purpose of the study: This study aims to develop and assess the effectiveness of a physics learning media based on songs and animations to enhance motivation and understanding among Grade VIII students on the topics of mirrors and lenses..Methodology: The study employed a mixed-methods approach, utilizing a procedural development model by Borg and Gall. Tools and software used include Adobe Audition 1.5, Wondershare Filmora, and Adobe Flash CS6. Data collection methods included questionnaires and expert reviews.Main Findings: The song and animation-based learning media received a "Very Valid" rating from content experts (90%) and a "Valid" rating from media experts (70%), with teachers giving an average score of 90%. The t-test results showed a significant increase in students' motivation in the experimental group, with a mean score of 79.50 compared to 68.07 in the control group, indicating the positive impact of the developed media.Novelty/Originality of this study: This study introduces an innovative approach by combining musical and animated elements in physics education, thereby stimulating both the left and right brain hemispheres. This dual-hemisphere engagement fosters a more interactive and enjoyable learning experience, bridging the gap in traditional physics instruction by addressing both logical and creative aspects of student learning.